The Development and Application of Positive Psychological Intervention Program for a College Ice Hockey Team - Jane Rhee; Sang-Hyun Kwon; Dong-Won Yook; Jung-Taek Shin (Cheyuk gwahag yeon-gu, 2021)
PURPOSE This study aimed to develop a positive psychological intervention program for a college ice hockey team and test its effects based on application to the team. METHODS The demands of 78 college ice hockey players were asked through open questionnaires. Collected results underwent integrated analysis to develop the desired program through the participants who were also observers of the team. The objectives of the program were established, and an appropriate program was developed based on the analyzed data, expert opinion, and precedent research. The developed program was applied to 26 players of a college ice hockey team to verify its effects. Tasks included writing experience reports and in-depth interviews. The Happiness Measures 1, Strength Knowledge, and Team Interaction Questionnaires were also administered. Collected qualitative data were categorized to follow inductive analysis procedures, while paired t-tests were performed for quantitative data using SPSS 25.0. RESULTS To improve the application of the program in real situations and maintain credibility and validity, the program was developed based on analyses of individual and team demands, methods of the participant as an observer, expert opinion, and other considerations. Statistically meaningful differences in positive psychological mind, happiness, recognition and utilization of strengths, team interactions, team cohesion, and so on were found using paired t-tests comparing data before and after the developed positive psychological intervention program. CONCLUSIONS Providing opportunities to recognize individual and team strengths and have valuable experiences for each player could enhance interactions between teammates and create a favorable team environment.